2017
DOI: 10.3390/biomedicines5040067
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anti-Thymocyte Globulin or Alemtuzumab-Based Serotherapy in the Prophylaxis and Management of Graft-Versus-Host Disease

Abstract: Allogeneic hematopoietic stem cell transplant is an established treatment modality for hematologic and non-hematologic diseases. However, it is associated with acute and long-term sequelae which can translate into mortality. Graft-versus-host disease (GVHD) remains a glaring obstacle, especially with the advent of reduced-intensity conditioning. Serotherapy capitalizes on antibodies which target T cells and other immune cells to mitigate this effect. This article focuses on the utility of two such agents: anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 103 publications
0
13
0
3
Order By: Relevance
“…No data could be extracted for the incidence of relapse, non-relapse mortality, grade III-IV acute GVHD, or GVHD relapse-free survival. The role of anti-thymocyte globulin (ATG) for acute GVHD prophylaxis has been well established in the literature, and ATG has been used at our institution; none of the patients in our study population from 2007-2017 received ATG [13]. As there is no comparator arm, outcomes were compared with the limited historical data available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…No data could be extracted for the incidence of relapse, non-relapse mortality, grade III-IV acute GVHD, or GVHD relapse-free survival. The role of anti-thymocyte globulin (ATG) for acute GVHD prophylaxis has been well established in the literature, and ATG has been used at our institution; none of the patients in our study population from 2007-2017 received ATG [13]. As there is no comparator arm, outcomes were compared with the limited historical data available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these antibody preparations have a long half-life in the human plasma and therefore, once administered as part of the conditioning regimen, they exert their biological effects for several weeks after the graft infusion and induce profound depletion of both host and donor immune cells (128,129). Moreover, besides the pan T-cell depletion (Figure 1), ATG and ALEM also mediated a variety of other immune effects [detailed in other informative reviews (130,131)]. Several large randomized phase 3 trials have demonstrated the benefit on both aand cGVHD incidence of adding ATG to standard prophylaxis in the setting of MAC-alloHCT with PBSC (122)(123)(124)(125)(126).…”
Section: How To Prevent Agvhd After Allohct? When the Clinician Meetsmentioning
confidence: 99%
“…These include ex vivo manipulation of the donor source including CD34 selection, TCRa/b and CD19 B cell depletion, and CD45RA T-cell depletion [27−29]. There are also in vivo depletion approaches including peritransplantation ATG [30], alemtuzumab [31], posttransplantation rituximab [32], and PTCy [33,34]. At this point, it is unclear which of these approaches offers the optimal approach.…”
Section: What About Other Donor Sources?mentioning
confidence: 99%